(untitled) (Global Journal of Human-Social Science, 2016)
It is against the background of the emerging trends in internally displacement of persons within the country and its associated camping needs that this study evaluates the realities of IDP camps with a view to proffering recommendation from urban planning perspective This study is an explorative one hence it benefits solely from secondary data which were obtained from existing literature and relevant governmental as well as non-governmental data banks It was however discovered that there is an increase in the number of IDPs from 868 335 in 2014 to 2 151 979 in 2015 which is caused by unfunded arguments in religious belief under development and poverty as well as unequal wealth among others Meanwhile the escalated number of IDPs has also been factored around increase in Boko Haram s terror act in recent years